Reforming Higher Education in the Middle Eastand Elsewhere - Altbach, Philip (International Higher Education, 2011)
The Arab Spring came, in part, from the region's universities. Students are central actors throughout the region. The weaknesses of the universities have been highlighted by these social movements. Additional funding, higher standards, and other improvements are needed. High levels of unemployment of graduates need also to be reduced.